Identifying uncertainty shocks using the price of gold - Michele Piffer; Maximilian Podstawski (Deutsches Institut für Wirtschaftsforschung (DIW), 2016)
We propose a new instrument to identify the impact of uncertainty shocks in a SVAR model with external instruments. We construct the instrument for uncertainty shocks by exploiting variations in the price of gold around selected events. The events capture periods of changes in uncertainty unrelated to other macroeconomic shocks. The variations in the price of gold around such events provide a measure correlated with the underlying uncertainty shocks, due to the perception of gold as a safe haven asset. The proposed approach improves upon the recursive identification of uncertainty shocks by not restricting only one structural shock to potentially affect all variables in the system. Replicating Bloom (2009), we find that the recursive approach underestimates the effects of uncertainty shocks and their role in driving monetary policy.
Keywords: E32; C32; D81; 330; economic uncertainty; external proxy SVAR; safe haven assets